Institutional framework and financial institutions management : three essays on banking in Africa - (:unkn) unknown (My University, 2019)
The banking system is underdeveloped in Africa. Banks are reluctant to lend, commit to shorter maturities, and enjoy higher net interest margins, while non-financial agents experience harsh difficulties in accessing the credit market. These characteristics reflect the institutional constraints faced by banks in their operations. This thesis contributes to a better understanding of these institutional constraints and their consequences on banking in Africa. Chapter 2 highlights how African banks’ ability to perform financial intermediation efficiently is determined by the protection level of borrowers and lenders, the contractual framework, and regulatory quality. Given these constraints, African banks hoard high levels of reserves while non-financial agents struggle to access to external finance. In chapter 3, we explain this paradox by the structurally low demand for credit induced by the deficiencies on the credit market. Lastly, African banks are adapting their business model to their operational context by shifting towards non-traditional banking. Chapter 4 shows that this shift has adverse consequences on the profitability and stability of smaller banks, which may lack the resources and capabilities necessary to engage in these new markets.
Keywords: African Research